A new nitronyl nitroxide radical with salicylic acid framework attenuates blood–brain barrier disruption and oxidative stress in a rat model of middle cerebral artery occlusion. Issue 3 (19th January 2022) - Chen, Lei; Ma, Shanbo; Shi, Min; Wang, Qiaofeng; Miao, Yi
Abstract : Objectives: A new nitronyl nitroxide radical with a salicylic acid framework (SANR) has been demonstrated to exert antioxidant effects in the previous study by our team. The current study has assessed the protective effect of SANR on cerebral ischemia and reperfusion (I/R) in rat models. Methods: Sprague–Dawley rats were randomly divided into four groups: sham, I/R, 10, and 20 mg/kg SANR + I/R groups. A total of 120 min of middle cerebral artery occlusion (MCAO) caused cerebral ischemia. Survival rates were calculated, and neurological deficits were evaluated by a blinded experimenter. Cerebral infarct area, apoptosis cells, and blood–brain barrier (BBB) leakage were measured by 2, 3, 5-triphenyltetrazolium chloride staining, terminal deoxynucleotidyl transferase dUTP nick-end labeling, and Evans blue assay, respectively. Reactive oxygen species (ROS), malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and 8-hydroxy-2-deoxyguanosine (8-OHdG) also were detected to assess oxidation damage caused by cerebral I/R. Results: Treatment with SANR significantly promoted survival of rats with cerebral I/R injury. SANR meliorated neurologic deficit and infarct area, improved BBB permeability, and reduced neuronal apoptosis. SANR also reduced ROS levels and the content of MDA and increased SOD and GSH-Px activity in a dose-dependent manner. Furthermore, SANR could inhibit the expression of 8-OHdG. Conclusion: Our results suggested that SANR has a neuroprotective effect against cerebral I/R injury, and its effect mechanism is related to the antioxidant function.